CURRENT FORMS OF ASSESSMENT IN PRIMARY EDUCATION WITH A FOCUS ON FORMATIVE ASSESSMENT (Proceedings of the International Conference on Education, 2021)
Assessment can be understood as an activity that pursues both the result as well as the process of achieving the goal, it monitors the conditions and means of achieving these goals and the activities of the pupil and teacher in the process of achieving goals. School assessment is a process that leads to determining the qualities and achievements showed by a pupil or a group of pupils; it is a systematic activity, i.e. prepared, organised and repeatedly performed, whereby the results are subject to revisions or corrections. Formative assessment is continuous feedback, where the learner obtains information in the learning process that compares the current situation with respect to the starting position and especially to the stated goal. The aim of our research was primarily to identify various forms of assessment at primary school and then to understand how teachers work with formative assessment in teaching practice. In view of the research objectives, a mixed research strategy was chosen. Within the quantitative survey, which focused on the assessment of various forms of assessment at school, a questionnaire of our own construction was used and was administered. The second step was implementing a qualitative survey, where semi-structured interviews were carried out focusing on the issue of format assessment in primary education. Results show that teachers often use alternative forms to the most common (summative) assessment in the form of pupils' portfolio, stamps, stickers, credits or letters. In terms of formative assessment, its contribution to pupils' development is appreciated as well as its greater informative value, but interestingly, many teachers use formative assessment without knowing that the chosen assessment method is known by this term.
Keywords: Primary education; school assessment; formative assessment; teaching methodology; methods of assessment